Pengembangan Media Pembelajaran Flipbook Interaktif Pada Mata Pelajaran Humas Dan Keprotokolan SMKN 12 Jakarta - Dzikra Alya; Darma Rika Swaramarinda; Ferry Setyadi Atmadja (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to develop an ADDIE-based interactive Flipbook media to improve student understanding. This study used the Research and Development (R&D) method. The results of the validation test showed that the interactive flipbook was very feasible to use, with an assessment of 90% from media experts, 86% from learning design, and 96% from materials. The media met the standards for appearance, content, and characteristics of vocational high school students. Revisions were made based on validator input. The effectiveness test resulted in an N-Gain of 0.75 (high category), indicating that the flipbook effectively improved understanding of public relations and protocol concepts through structured presentation, attractive visuals, and interactive quizzes. The results showed that the media development process was systematic and produced an interactive flipbook that met the needs of vocational high school students. The media was declared feasible, effective, and received positive responses from students, and can be applied to vocational learning of Public Relations and Protocol.